A Monitoring System for Sustainable Urban Mobility Plans - Jonas Damidavičius; Marija Burinskienė; Rasa Ušpalytė−Vitkūnienė (The Baltic Journal of Road and Bridge Engineering)
Sustainable Urban Mobility Plans are developed in Europe rapidly. The future initiative is expected will change the image of European cities and will make transport systems efficacious, thus reducing congestion, decreasing air pollution, and offering alternative options for travelling. The impact of the measures being implemented needs to be monitored regularly to evaluate the effect of Sustainable Urban Mobility Plans, and progress in accomplishing the objectives and specific aims of Sustainable Urban Mobility Plans are assessed. Infrastructure measures often require considerable investment, and therefore, their rational use expected to create immense benefit to the public. This article analyses various European models for monitoring and evaluating Sustainable Urban Mobility Plans. The models are structured, proposing an assessment methodology for Sustainable Urban Mobility Plans. Assistance provided by the experts and the use of evaluation models for the analytic hierarchy process assists in identifying the significance of the monitoring indicators that allow assessing the priority orders and the importance of implementing mobility measures.